Pengembangan Karakter Peserta Didik Berbasis Pendidikan Agama Islam (Penelitian di SMA Ksatria Nusantara Boarding School Kecamatan Padaherang Kabupaten Pangandaran) - Thoyyibah, Ita; Setiawan, Iwan (Graduate Program, Universitas Islam Darussalam (UID) | Islamic University of Darussalam, 2018)
This research assumes that religious teachings can be the foundation and foundation for character education. This research can prove the truth of this assumption. This research assumes that religious teachings can be the foundation and foundation for character education. This study tries to prove the truth of these assumptions. The study uses descriptive analysis method. Data obtained by interview, observation, study of school documents. Interviews were conducted with a number of informants, ranging from students, teachers, students' parents, and the community around the school. The results of this study confirm that religious education can be a source for character education. The values of patience, honesty, discipline, responsibility, respect, respect, courtesy, and love to read are the main character values in the Islamic religion.